Gene characteristics, immune and stress responses of PmPrx1 in black tiger shrimp (Penaeus monodon): Insights from exposure to pathogenic bacteria and toxic environmental stressors. (December 2017) - Bu, Ruiqian; Wang, Pengfei; Zhao, Chao; Bao, Weiyang; Qiu, Lihua
Abstract: Peroxiredoxins (Prxs) are ubiquitous, multifunctional and evolutionarily conserved enzymes that can protect cells from oxidative damage caused by ROS and play a vital role in immune responses. Here, a full-length Prx1 cDNA sequence ( PmPrx1 ) was isolated from Penaeus monodon . The PmPrx1 cDNA was 951 base pairs (bp), encoding 198 amino acid polypeptides. The results of qRT-PCR showed that the PmPrx1 mRNA was ubiquitously expressed in all tissues tested and had a comparatively high expression level in immune-associated tissues (gill, hepatopancreas). To explore the immune and anti-stress roles of PmPrx1, the gills and hepatopancreas were chosen as target tissues in Penaeus monodon and were challenged with bacteria ( Vibrio harveyi and Streptococcus agalactiae ) and toxic environmental stresses. To further clarify the immune function of PmPrx1 after bacterial challenge, the recombinant PmPrx1 protein was acquired using a prokaryotic expression method. The antioxidant activity of the recombinant PmPrx1 was assessed by the catalyzing hydrogen peroxide assay method, and the results showed obvious antioxidant activity in a dose-dependent and temperature-dependent manner. The antimicrobial activity of purified PmPrx1 protein was evaluated and further studied in vitro relying on a bacterial growth inhibition test which was conducted in both liquid and solid cultu res. Furthermore, E. coli transferred with pRSET-PmPrx1 was dramatically protected in response to metal toxicity and H2 O2 oxidative stress. In summary, this study provides useful information about the role of the Prx1 gene in defense against a variety of toxic factors in shrimps that help to further clarify the functional mechanism of Prx. Highlights: PmPrx1 gene was identified and characterised in Penaeus monodon . The results of qRT-PCR showed that the PmPrx1 mRNA was ubiquitously expressed. The antioxidant activity of the recombinant PmPrx1 was assessed. The antibacterial activity of the purified PmPrx1 protein was further studied in vitro .